High-performance corrosion-resistant magnesium alloy suitable for prestress loading condition as well as preparation method and application of high-performance corrosion-resistant magnesium alloy
By optimizing the composition and preparation process of magnesium alloy, including mixed smelting, refining, casting, homogenization treatment and hot extrusion, the problem of uncontrollable residual stress in magnesium alloy preparation is solved, and the performance and stability of magnesium alloy under prestressed loading conditions is improved.
Patent Information
- Application Number
- CN202510005867.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
AI Technical Summary
Existing magnesium alloy preparation technology is difficult to effectively control the cooling rate of materials and mold design, resulting in uncontrollable and uneven distribution of residual stresses in the finished product, affecting the performance of magnesium alloys and the stability of the processing process.
By optimizing the alloy composition and preparation process, pure Mg, pure Zr, Mg-30Gd intermediate alloy and Mg-30Y intermediate alloy are used as raw materials to perform mixed smelting, refining, casting, homogenization treatment and hot extrusion to achieve effective control of the internal stress of magnesium alloy.
It effectively reduces the adverse impact of prestress on the performance of magnesium alloys, improves the application potential of materials in high-demand environments, and enhances the performance and stability of magnesium alloys under extreme conditions.
Smart Images

Figure CN119800136A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metal material preparation, and in particular relates to a high-performance corrosion-resistant magnesium alloy suitable for prestressed loading conditions, and a preparation method and application thereof. Background Art
[0002] Magnesium alloys have been widely used in aerospace, automotive, and electronics fields due to their light weight, high strength, and good processing properties. In recent years, with the increasing demand for high-performance materials, researchers have invested a lot of energy in improving the performance and expanding the application of magnesium alloys. However, prestress often occurs during the production and processing of magnesium alloys. These prestresses mainly come from factors such as uneven shrinkage of the material during cooling and solidification, friction between the mold and the material, and changes in the internal microstructure of the material. These factors not only affect the final properties of the magnesium alloy, but may also cause defects during processing, such as deformation and cracking.
[0003] There are still some technical problems in the existing technology for prestress management of magnesium alloys. For example, the traditional preparation method often cannot effectively control the cooling rate of the material and the mold design, resulting in uncontrollable and uneven distribution of residual stress in the finished product. Summary of the invention
[0004] In view of the deficiencies of the above-mentioned prior art, the purpose of the present invention is to provide a high-performance corrosion-resistant magnesium alloy suitable for prestressed loading conditions and its preparation method and application. The present invention aims to achieve effective control of the internal stress of the magnesium alloy by optimizing the alloy composition and preparation process, thereby improving the stability and reliability of the material under complex loading conditions. This method can not only solve the residual stress problem existing in traditional preparation technology, but also enhance the performance of magnesium alloy under extreme conditions, and provide a safer and more reliable material selection for related applications. Through the implementation of the present invention, the adverse effects of prestress on the performance of magnesium alloy can be effectively reduced, and its application potential in high-demand environments can be improved, promoting the further development and application of magnesium alloy materials.
[0005] In order to solve the above technical problems, the present invention adopts the following technical methods: A method for preparing a high-performance corrosion-resistant magnesium alloy suitable for prestressed loading conditions comprises the following steps: Pure Mg, pure Zr, Mg-30Gd master alloy and Mg-30Y master alloy are used as raw materials, and 4.5wt.%~10.5wt.% Gd, 2.0wt.%~4.5wt.% Y, 0.3wt.%~0.6wt.% Zr and the balance Mg are mixed and smelted.
[0006] After smelting, it is refined and cast.
[0007] After casting, the alloy is homogenized and hot extruded to obtain a high-performance magnesium alloy.
[0008] The second object of the present invention is to provide a high-performance magnesium alloy obtained by the preparation method described in any one of the above items, wherein the magnesium alloy comprises, by mass percentage, 10%~13%Gd: 1%~3%Y, 0.5%Zr, the remainder is Mg, and the alloy is 100%.
[0009] In a preferred embodiment of the present invention, the high performance corrosion-resistant magnesium alloy suitable for use under prestressed loading conditions comprises, by mass percentage, 7% to 10.5% Gd, 3% to 4.5% Y, 0.5% to 0.6% Zr, and the remainder is Mg, totaling 100%.
[0010] The third object of the present invention is to provide an application of the high performance magnesium alloy described above in magnesium alloy parts under prestressed loading conditions.
[0011] Preparation of magnesium alloys Raw material ratio range: 99.99% pure magnesium accounts for the main body, Mg-30Gd master alloy accounts for 4.5%-10.5%, Mg-30Y master alloy accounts for 2.0%-4.5%, and high-purity 99.99% zirconium accounts for 0.3%-0.6%.
[0012] The optimal raw material ratio: 99.99% pure magnesium, 7% Mg-30Gd master alloy, 3% Mg-30Y master alloy, and 0.5% 99.99% pure zirconium.
[0013] Melting temperature range: 680°C~760°C; optimal melting temperature: 720°C; stirring speed range: 200 RPM~400RPM; optimal stirring speed: 300 RPM.
[0014] Refining time range: 5 minutes ~ 15 minutes; optimal refining time: 10 minutes; casting mold preheating temperature range: 200°C ~ 300°C; optimal mold preheating temperature: 250°C.
[0015] Homogenization temperature range: 380°C~420°C; optimal homogenization temperature: 400°C; homogenization time range: 10 hours~14 hours; optimal homogenization time: 12 hours; hot extrusion ratio range: 14~18:1; optimal hot extrusion ratio: 16:1; extrusion speed range: 0.5 mm / s~1.5 mm / s; optimal extrusion speed: 1 mm / s.
[0016] Pure magnesium uses industrial grade magnesium with a purity of ≥99.99%. It is mainly sourced from professional metal suppliers. This high-purity magnesium plays a basic role in alloy preparation, ensuring the physical and chemical properties of the alloy, enabling it to maintain excellent mechanical properties and corrosion resistance during subsequent processing.
[0017] Mg-30Gd master alloy: This alloy contains 30% gadolinium, which is a key component for improving the strength and heat resistance of magnesium alloys. The addition of gadolinium not only helps to improve the crystal structure of the alloy, but also significantly improves its creep resistance. The master alloy purchased comes from a professional alloy material supplier, ensuring the stability and consistency of its composition.
[0018] Mg-30Y master alloy: Similarly, this alloy contains 30% yttrium, which is designed to further enhance the performance of magnesium alloys. The addition of yttrium can increase the alloy's oxidation resistance and improve its corrosion resistance. This master alloy is also provided by a professional alloy material supplier, ensuring its quality and reliability.
[0019] High-purity 99.99% zirconium: As an important additive in alloys, high-purity zirconium has excellent corrosion resistance and strengthening effects. Its high purity ensures uniform distribution and performance stability in the alloy. The purchased zirconium material also comes from a professional metal supplier to ensure its quality standards.
[0020] Raw material dosage: High-purity 99.99% magnesium: In this alloy formula, high-purity magnesium accounts for the main part of the total mass of the alloy and provides basic mechanical properties and stability as a matrix material.
[0021] Mg-30Gd master alloy: The amount of this alloy accounts for 7% of the total mass of the alloy, providing a strengthening phase for the alloy and improving the strength and toughness of the alloy through interaction with the magnesium matrix.
[0022] Mg-30Y master alloy: accounts for 3% of the total mass of the alloy. Its main function is to enhance the alloy's high temperature resistance and corrosion resistance, and ensure its reliability in various working environments.
[0023] High-purity 99.99% zirconium: Although it accounts for only 0.5%, the addition of zirconium is crucial to improving the mechanical properties of the alloy. By optimizing the microstructure, the mechanical strength is improved, allowing the alloy to maintain excellent performance in harsh environments.
[0024] Process flow and parameters Raw material preparation: Before alloy preparation, accurately weigh the required high-purity magnesium, Mg-30Gd master alloy, Mg-30Y master alloy and high-purity zirconium, and strictly mix them according to the above ratio. This step ensures the accuracy of the composition and the uniformity of the alloy, providing the necessary basis for subsequent smelting.
[0025] Melting: The weighed raw materials are placed in a light steel crucible preheated to room temperature, and a mixed gas of SF6 and CO2 is used as a protective atmosphere to avoid oxidation reactions under high temperature conditions. The temperature is heated to 720°C using a resistance furnace and maintained until all the raw materials are completely melted and evenly mixed. This step is critical to the quality of the alloy and ensures the full fusion of the alloying elements.
[0026] Stirring: The molten metal is stirred at 300 RPM for 10 minutes at 720°C. This step helps to enhance the uniform distribution of the components in the alloy and ensures sufficient mixing between different elements, thereby improving the overall performance of the alloy.
[0027] Refining: Add a specific refining agent to the molten metal and continue stirring for 5 to 15 minutes to remove impurities and slag in the molten metal. The refining process is an important step in improving the purity of the alloy, which helps to eliminate defects in the alloy and improve its mechanical properties.
[0028] Casting: The refined molten metal is poured into a steel mold preheated to 250°C to form an ingot. During the casting process, preheating the mold helps reduce temperature gradients, reduce casting defects, and improve the density of the ingot.
[0029] Homogenization treatment: The ingot is homogenized at 400°C for 12 hours. This step is to eliminate component segregation, promote the homogenization of the microstructure, and ensure the consistency and stability of the alloy in subsequent processing.
[0030] Hot extrusion: The homogenized ingot was hot extruded at 400°C with an extrusion ratio of 16:1. The extrusion was performed using a hydraulic press at a speed of 1 mm / s. This process not only improved the density of the alloy but also optimized its mechanical properties.
[0031] Cooling: The extruded alloy is cooled to room temperature in air to ensure that the shape of the material is stable during the cooling process and to avoid internal stress.
[0032] Cutting and sampling: Cut the cooled extruded alloy into the required specimens for subsequent microstructure analysis and mechanical property testing. This step provides the necessary experimental basis for subsequent research and application, ensuring the representativeness of the samples and the reliability of the experimental data.
[0033] Through the above method, a high-performance corrosion-resistant magnesium alloy suitable for prestressed loading conditions can be successfully prepared from raw materials.
[0034] The beneficial effects of the present invention are: 1. The preparation method of the present invention tries to keep the wall thickness uniform and avoid sudden changes in wall thickness during design, so as to reduce the uneven shrinkage during the cooling process. Larger fillets are used at the corners and joints of the parts to reduce stress concentration, simplify the part structure, reduce unnecessary complex shapes, and reduce the generation of internal stress; select appropriate alloy elements and proportions to improve the overall performance of the material and reduce the generation of internal stress. The present invention uses Gd, Zr and Y elements to form an alloy, wherein the addition of Y element helps to improve the yield strength and tensile strength of the magnesium alloy, and also improves its corrosion resistance. The uniformity of the material is improved and the internal stress is reduced by grain refinement technology, such as adding a grain refiner. The present invention uses the Gd element: adding Gd can improve the strength and heat resistance of the magnesium alloy, and Gd can also promote grain refinement, thereby improving the mechanical properties of the alloy. The present invention also uses the Zr element: Zr is a commonly used grain refiner, which can form fine primary grains, can effectively refine the grains of the magnesium alloy, and improve its strength and plasticity. In addition, during the smelting process, stirring and specific refining agents can promote the uniform distribution of alloy elements and create conditions for grain refinement. The subsequent homogenization treatment, the ingot in this experimental scheme is homogenized at 400°C for 12 hours, which helps to eliminate component segregation and provide a uniform microstructure for subsequent hot extrusion. After heat treatment, a hot deformation process is adopted, which can not only change the shape of the material but also further refine the grains through hot extrusion. The extrusion ratio of 22:1 and the appropriate extrusion temperature of 425°C in the present invention help to obtain a fine grain structure.
[0035] 2. The high-performance magnesium alloy developed by the present invention is designed for application under prestressed loading conditions and exhibits excellent mechanical properties. -6The slow tensile test shows that the magnesium alloy can still maintain good strength and ductility at extremely low strain rates, indicating its reliability under complex load conditions. This performance is maintained thanks to the optimized alloy composition and preparation process, which effectively reduces the internal residual stress and improves the uniformity of the microstructure of the material. When the magnesium alloy designed by the present invention serves in a structural part that bears long-term loads, its safety and reliability will be significantly improved. Its application scope covers: 1) Aerospace, used to improve the long-term service of magnesium alloy parts in aircraft; 2) Automobile industry, used to design and manufacture lightweight automobile parts, especially magnesium alloy die-castings, so that their reliability under load conditions is greatly improved; 3) In certain lightweight and high-strength building materials, magnesium alloys may be used in truss structures and slings of cross-sea bridges to reduce the overall weight and improve earthquake resistance, while requiring a certain degree of corrosion resistance; in disaster area reconstruction or temporary activities, the lightness and easy processing of magnesium alloy support frames can speed up construction, and these magnesium alloys are often subject to loads during application and service, and even subject to the dual effects of stress-saltwater corrosion under conditions adjacent to the coast. Therefore, the high-performance corrosion-resistant magnesium alloy under prestressed loading conditions of the present invention will focus on solving the above-mentioned urgent needs.
[0036] 3. The excellent performance of the alloy of the present invention provides new possibilities for its application in the fields of aerospace, marine engineering and automobile. In practical applications, the material not only needs to withstand high loads and impacts, but also needs to have the ability to serve in an environment of alternating slow strain and corrosion to ensure long-term stability in complex environments. Through the research and development of the present invention, it is expected to promote the widespread application of high-performance magnesium alloys and provide safer and more reliable material solutions for related industries. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 FIG. 4 is a diagram of a tensile test device according to the present invention.
[0038] Figure 2 The high performance corrosion resistant magnesium alloy prepared in Example 1 of the present invention was heated to 5×10 -6 Stress-strain diagram after strain rate tensile fracture.
[0039] Figure 3 The high performance corrosion resistant magnesium alloy prepared in Example 1 of the present invention was heated to 5×10 -6 Optical image of the metal morphology after strain rate tensile fracture.
[0040] Figure 4 The high performance corrosion resistant magnesium alloy prepared in Example 1 of the present invention was heated to 5×10 -6 Metal morphology after strain rate tensile fracture - surface macroscopic image under electron microscope.
[0041] Figure 5 The high performance corrosion resistant magnesium alloy prepared in Example 1 of the present invention was heated to 5×10 -6 Metal morphology after strain rate tensile fracture - high-magnification surface image under electron microscope.
[0042] Figure 6 The high performance corrosion resistant magnesium alloy prepared in Example 1 of the present invention was heated to 5×10 -6 Metal morphology after strain rate tensile fracture - low-magnification fracture image under electron microscope.
[0043] Figure 7 The high performance corrosion resistant magnesium alloy prepared in Example 1 of the present invention was heated to 5×10 -6 Metal morphology after strain rate tensile fracture - high-magnification fracture image under electron microscope.
[0044] Figure 8 The high performance corrosion resistant magnesium alloy prepared in Example 2 of the present invention was heated to 5×10 -6 Stress-strain diagram after strain rate tensile fracture.
[0045] Fig. 9 The high performance corrosion resistant magnesium alloy prepared in Example 2 of the present invention was heated to 5×10 -6 Optical image of the metal morphology after strain rate tensile fracture.
[0046] Fig.10 The high performance corrosion resistant magnesium alloy prepared in Example 2 of the present invention was heated to 5×10 -6 Metal morphology after strain rate tensile fracture - surface macroscopic image under electron microscope.
[0047] Fig.11 The high performance corrosion resistant magnesium alloy prepared in Example 2 of the present invention was heated to 5×10 -6 Metal morphology after strain rate tensile fracture - high-magnification surface image under an electron microscope.
[0048] Fig.12 The high performance corrosion resistant magnesium alloy prepared in Example 2 of the present invention was heated to 5×10 -6 Metal morphology after strain rate tensile fracture - low-magnification image of the fracture under an electron microscope.
[0049] Fig.13 The high performance corrosion resistant magnesium alloy prepared in Example 2 of the present invention was heated to 5×10 -6 Metal morphology after strain rate tensile fracture - high-magnification image of the fracture under an electron microscope.
[0050] Fig.14 This is a stress-strain curve of a traditional magnesium alloy with Mg-Gd-Y-Zr component prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0051] The following is a detailed description of the technical solutions in the embodiments of the present invention in combination with the preferred embodiments and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0052] It should be noted that all professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.
[0053] Example 1 A method for preparing a high-performance corrosion-resistant magnesium alloy suitable for prestressed loading conditions comprises the following steps: (1) Weigh the following raw materials by mass percentage: 7% Gd, 3% Y, 0.5% Zr, and the balance Mg, totaling 100%.
[0054] (2) Place the weighed raw materials in a light steel crucible preheated to room temperature, heat the temperature to 720°C using a resistance furnace, and maintain this temperature until all the raw materials are completely melted and evenly mixed.
[0055] (3) Stir the molten metal at 720°C at a speed of 300 RPM for 10 minutes.
[0056] (4) Add calcium fluoride as a refining agent to the molten metal in an amount of 2% of the mass of the molten metal, and continue stirring for 10 minutes to remove impurities and slag in the molten metal.
[0057] (5) The refined molten metal is poured into a steel mold preheated to 250°C for casting to form an ingot.
[0058] (6) The ingot is homogenized at 400°C for 12 hours, and the ingot after homogenization is hot extruded. The extrusion temperature is maintained at 400°C, the extrusion ratio is set to 16:1, and a hydraulic press is used to extrude at a speed of 1 mm / s. The extruded alloy is cooled to room temperature in air to ensure that the shape of the material is stable during the cooling process and to avoid the generation of internal stress, so as to obtain a high-performance magnesium alloy.
[0059] Example 2 A method for preparing a high-performance corrosion-resistant magnesium alloy suitable for prestressed loading conditions comprises the following steps: (1) Weigh the following raw materials by mass percentage: 6% Gd, 4% Y, 0.5% Zr, and the balance Mg, totaling 100%.
[0060] (2) Place the weighed raw materials in a light steel crucible preheated to room temperature, heat the temperature to 720°C using a resistance furnace, and maintain this temperature until all the raw materials are completely melted and evenly mixed.
[0061] (3) Stir the molten metal at 720°C at a speed of 300 RPM for 10 minutes.
[0062] (4) Add calcium fluoride as a refining agent to the molten metal in an amount of 2% of the mass of the molten metal, and continue stirring for 10 minutes to remove impurities and slag in the molten metal.
[0063] (5) The refined molten metal is poured into a steel mold preheated to 250°C for casting to form an ingot.
[0064] (6) The ingot is homogenized at 400°C for 12 hours, and the ingot after homogenization is hot extruded. The extrusion temperature is maintained at 400°C, the extrusion ratio is set to 16:1, and a hydraulic press is used to extrude at a speed of 1 mm / s. The extruded alloy is cooled to room temperature in air to ensure that the shape of the material is stable during the cooling process and to avoid the generation of internal stress, so as to obtain a high-performance magnesium alloy.
[0065] Example 3 A method for preparing a high-performance corrosion-resistant magnesium alloy suitable for prestressed loading conditions comprises the following steps: (1) Weigh the following raw materials by mass percentage: 4.5% Gd, 2.0% Y, 0.3% Zr, and the balance Mg, totaling 100%.
[0066] (2) Place the weighed raw materials in a light steel crucible preheated to room temperature, heat the temperature to 680°C using a resistance furnace, and maintain this temperature until all the raw materials are completely melted and evenly mixed.
[0067] (3) Stir the molten metal at 680°C at a speed of 200 RPM for 10 minutes.
[0068] (4) Add calcium fluoride as a refining agent to the molten metal in an amount of 2% of the mass of the molten metal, and continue stirring for 5 minutes to remove impurities and slag in the molten metal.
[0069] (5) The refined molten metal is poured into a steel mold preheated to 200°C for casting to form an ingot.
[0070] (6) The ingot is homogenized at 380°C for 10 hours, and the ingot after homogenization is hot extruded. The extrusion temperature is maintained at 400°C, the extrusion ratio is set to 14:1, and a hydraulic press is used to extrude the ingot at a speed of 0.5 mm / s. The extruded alloy is cooled to room temperature in air to ensure the shape stability of the material during the cooling process and avoid the generation of internal stress, so as to obtain a high-performance magnesium alloy.
[0071] Example 4 A method for preparing a high-performance corrosion-resistant magnesium alloy suitable for prestressed loading conditions comprises the following steps: (1) Weigh the following raw materials by mass percentage: 10.5% Gd, 4.5% Y, 0.6% Zr, and the balance Mg, totaling 100%.
[0072] (2) Place the weighed raw materials in a light steel crucible preheated to room temperature, heat the temperature to 760°C using a resistance furnace, and maintain this temperature until all the raw materials are completely melted and evenly mixed.
[0073] (3) Stir the molten metal at 760°C and 400 RPM for 10 minutes.
[0074] (4) Add calcium fluoride as a refining agent to the molten metal in an amount of 2% of the mass of the molten metal, and continue stirring for 15 minutes to remove impurities and slag in the molten metal.
[0075] (5) The refined molten metal is poured into a steel mold preheated to 300°C for casting to form an ingot.
[0076] (6) The ingot is homogenized at 420°C for 14 hours, and the ingot after homogenization is hot extruded. The extrusion temperature is maintained at 400°C, the extrusion ratio is set to 18:1, and a hydraulic press is used to extrude the ingot at a speed of 1.5 mm / s. The extruded alloy is cooled to room temperature in air to ensure the shape stability of the material during the cooling process and avoid the generation of internal stress, so as to obtain a high-performance magnesium alloy.
[0077] Comparative Example 1 The preparation process of the conventional Mg-Gd-Y-Zr component magnesium alloy comprises the following steps: (1) Weigh the following raw materials by mass percentage: 10% Gd, 2% Y, 1% Zr, and the balance Mg.
[0078] (2) The weighed raw materials were placed in a heavy casting crucible preheated to 300°C, and the temperature was heated to 800°C using an electric arc furnace. The temperature was maintained for 3 hours to ensure that the raw materials were fully melted and evenly mixed.
[0079] (3) Stir the molten metal at 800°C at a speed of 100 RPM for 15 min. Increase the stirring time to improve uniformity.
[0080] (4) Add calcium fluoride as a refining agent to the molten metal in an amount of 2% of the mass of the molten metal and continue stirring for 15 minutes to effectively remove impurities and slag in the molten metal.
[0081] (5) The refined molten metal is poured into an aluminum mold preheated to 400°C for casting to form an ingot, and the casting temperature is increased to reduce casting defects.
[0082] (6) The ingot was homogenized at 450°C for 24 h, cooled, and then hot extruded. The extrusion temperature was maintained at 400°C, the extrusion ratio was set to 16:1, and a hydraulic press was used to extrude at a speed of 1 mm / s to ensure the shape stability of the material and obtain a conventional magnesium alloy.
[0083] Results Analysis Figure 2 The high performance corrosion resistant magnesium alloy prepared in Example 1 of the present invention was heated to 5×10 -6 The stress-strain diagram after strain rate tensile fracture shows that the alloy exhibits excellent plasticity and strength during the tensile process, and the yield point and tensile strength are significantly higher than those of traditional magnesium alloys. The results show that the high-performance magnesium alloy has good mechanical properties and is suitable for use in loaded service.
[0084] The stress-strain curve of the conventional magnesium alloy in air in Comparative Example 1: yield strength: about 150 MPa, tensile strength: about 250 MPa, elongation: about 10%.
[0085] Figure 3 The high performance corrosion resistant magnesium alloy prepared in Example 1 of the present invention was heated to 5×10 -6 The optical image of the metal morphology after strain rate tensile fracture shows that the fracture surface of the alloy shows fewer cracks and better surface quality, which indicates that the material has good plastic deformation ability during the tensile process. The results show that the high-performance magnesium alloy can effectively resist crack propagation at high strain rates, has excellent toughness and corrosion resistance, and is suitable for application under extreme conditions.
[0086] Figure 4The high performance corrosion resistant magnesium alloy prepared in Example 1 of the present invention was heated to 5×10 -6 The metal morphology after strain rate tensile fracture - surface macroscopic image under electron microscope, and there are no obvious cracks or defects, indicating that the material maintains good integrity during the tensile process. The results show that the high-performance magnesium alloy exhibits excellent deformation resistance and high toughness under tensile stress, further verifying its superior performance in harsh environments.
[0087] Figure 5 The high performance corrosion resistant magnesium alloy prepared in Example 1 of the present invention was heated to 5×10 -6 The metal morphology after strain rate tensile fracture - high-magnification surface image under electron microscope, according to Figure 5 , you can see obvious dimple-shaped fracture surfaces or ductile pits. The formation of these dimples is due to the fact that during the plastic deformation of the material, dislocation movement leads to local plastic flow, and finally a series of pits are formed on the fracture surface. The presence of more dimples actually reflects the excellent tensile properties of the material during the stretching process, which is specifically reflected in the following aspects. 1. Plastic deformation ability: The formation of dimples indicates that the material can withstand large plastic deformation without immediate fracture during the stretching process, which shows that the high-performance corrosion-resistant magnesium alloy designed under prestressed loading conditions of the present invention meets the requirements, and at the same time Figure 1 From the stress-strain curve in the figure, it can be seen that its slow tensile elongation in air is as high as 18%, and its tensile strength is close to 300MPa, showing excellent mechanical properties and outstanding processability. Its excellent plasticity makes it more resilient and adaptable in practical applications, while its high tensile strength ensures its reliability under various extreme conditions. These characteristics make the material have great potential in high-demand applications such as unmanned underwater vehicles, and it is an ideal choice for achieving higher performance. It can absorb external energy to a certain extent, thereby providing better safety and reliability when subjected to external forces, thereby realizing the design significance of the present invention. 2. At the same time, the dimples also show that the high-performance corrosion-resistant magnesium alloy designed by the present invention for prestressed loading conditions has good toughness: the presence of dimples is usually closely related to the toughness of the material. Toughness refers to the energy that a material can absorb before breaking. More dimples mean that the material can absorb more energy before breaking and show higher toughness, which is crucial to preventing sudden fractures and improving the safety of the structure. The above results not only verify the excellent mechanical properties of the designed high-performance corrosion-resistant magnesium alloy suitable for prestressed loading conditions during the tensile process, but also emphasize its safety and reliability in practical applications.
[0088] Figure 6 The high performance corrosion resistant magnesium alloy prepared in Example 1 of the present invention was heated to 5×10 -6The metal morphology after strain rate tensile fracture - low magnification fracture image under electron microscope. It can be seen from the figure that the fracture of the alloy shows obvious dimple structure, indicating that the alloy exhibits good toughness and plastic deformation ability during the tensile process. The results show that the high-performance magnesium alloy has excellent crack propagation resistance and is suitable for long-term service under complex load conditions.
[0089] Figure 7 The high performance corrosion resistant magnesium alloy prepared in Example 1 of the present invention was heated to 5×10 -6 Metal morphology after strain rate tensile fracture - high-magnification fracture image under electron microscope. It can be seen from the figure that the fracture surface of the alloy presents a delicate microstructure, and the obvious dimples and microcracks indicate that the material has undergone significant plastic deformation during the tensile process. The results show that the high-performance magnesium alloy has good energy absorption capacity and crack propagation resistance under stress, proving its excellent performance under high strain conditions and suitable for applications in high loads and extreme environments.
[0090] Figure 8 The high performance corrosion resistant magnesium alloy prepared in Example 2 of the present invention was heated to 5×10 -6 The stress-strain diagram after strain rate tensile fracture shows that the alloy still exhibits good plasticity and strength in a corrosive environment. Although the yield strength and tensile strength are reduced, they are still higher than the level of traditional magnesium alloys. The results show that the alloy has excellent corrosion resistance.
[0091] Fig. 9 The high performance corrosion resistant magnesium alloy prepared in Example 2 of the present invention was heated to 5×10 -6 Optical image of the metal morphology after strain rate tensile fracture. It can be seen from the figure that the fracture surface of the alloy presents a uniform microstructure and no obvious corrosion damage occurs on the surface. The results show that the alloy has excellent corrosion resistance and mechanical properties in a corrosive environment and is suitable for application in harsh environments.
[0092] Fig.10 The high performance corrosion resistant magnesium alloy prepared in Example 2 of the present invention was heated to 5×10 -6 Metal morphology after strain rate tensile fracture - surface macroscopic image under electron microscope. It can be seen from the figure that the surface structure of the alloy is uniform and smooth, showing fewer cracks and defects, indicating that the material exhibits good corrosion resistance and toughness in a corrosive environment. The results show that this high-performance magnesium alloy can effectively resist oxidation and corrosion under extreme conditions and is suitable for engineering applications in marine and other harsh environments.
[0093] Fig.11The high performance corrosion resistant magnesium alloy prepared in Example 2 of the present invention was heated to 5×10 -6 The metal morphology after strain rate tensile fracture - high-magnification surface image under an electron microscope. It can be seen from the figure that the surface of the alloy presents delicate microstructural characteristics without obvious defects. The results show that the alloy exhibits excellent toughness and crack growth resistance in corrosive media, and is suitable for applications in harsh environments.
[0094] Fig.12 The high performance corrosion resistant magnesium alloy prepared in Example 2 of the present invention was heated to 5×10 -6 Metal morphology after strain rate tensile fracture - low magnification image of the fracture under an electron microscope. It can be seen from the figure that the fracture surface of the alloy shows obvious dimple structure, indicating that it has undergone significant plastic deformation during the tensile process. The overall fracture is uniform, without obvious brittle fracture characteristics, showing good toughness. The results show that the high-performance magnesium alloy maintains excellent mechanical properties in a corrosive environment and is suitable for application under complex and harsh conditions.
[0095] Fig.13 The high performance corrosion resistant magnesium alloy prepared in Example 2 of the present invention was heated to 5×10 -6 The metal morphology after strain rate tensile fracture - high magnification image of the fracture under an electron microscope. It can be seen from the figure that the alloy fracture surface has delicate microstructural characteristics, and the microcrack characteristics show that the material has undergone effective plastic and toughness deformation during the tensile process. The results show that the high-performance magnesium alloy exhibits certain toughness and crack propagation resistance in a corrosive environment, indicating its application potential under harsh conditions.
[0096] Fig.14 This is a stress-strain curve diagram of a conventional magnesium alloy with Mg-Gd-Y-Zr component prepared in comparative example 1 of the present invention. It can be seen from the figure that the alloy exhibits lower yield strength and tensile strength during stretching, and has relatively limited strain capacity, showing obvious brittle fracture characteristics. The results indicate that conventional magnesium alloys are inferior to the high-performance corrosion-resistant magnesium alloys of the present invention in terms of mechanical properties, emphasizing the necessity of using high-performance alloys in high-strain environments.
[0097] In Example 2, the excellent performance of the Mg-Gd-based high-performance corrosion-resistant magnesium alloy prepared by the present invention in a simulated seawater environment is further verified. In a 3.5% NaCl solution, although the plasticity of the magnesium alloy is reduced compared to that in a dry air environment, reaching 6.5%, this value is still within an acceptable range, indicating that the alloy still maintains a certain deformation ability in a saltwater environment. More significantly, its tensile strength is maintained at a high level of about 225MPa, which fully demonstrates the high strength retention ability of the magnesium alloy in a harsh corrosive environment. In addition, the performance of the magnesium alloy in a seawater solution not only reflects its excellent corrosion resistance, but also reflects its potential value in practical applications. In the fields of marine engineering, shipbuilding, submarine cables, etc., the application of this high-performance corrosion-resistant magnesium alloy will greatly improve the reliability and service life of the structure. At the same time, its higher tensile strength ensures that under prestressed loading conditions, the alloy can withstand greater external forces and is not prone to fracture, thereby ensuring the safety and stability of the project.
[0098] A conventional magnesium alloy with Mg-Gd-Y-Zr composition different from the process of the present invention is given, and the same is done at room temperature in a laboratory air environment at 1*10 -6 / s strain rate for stretching, here is the stress-strain curve of the traditional magnesium alloy with Mg-Gd-Y-Zr component, it can be seen that its elongation in air is only 7.8%, which is much lower than the elongation of 18% in this solution. In addition, the comparison of the mechanical property curves of the two magnesium alloys in air also reveals the advantages of the magnesium alloy of the present invention in mechanical properties, especially the substantial improvement in elongation, which not only reflects the optimization of the alloy microstructure, but also reflects the effectiveness of the process of the present invention in improving the comprehensive performance of the material. Traditional magnesium alloys with lower elongation may encounter risks due to insufficient plasticity in application, while the magnesium alloy in this solution can better adapt to various stress conditions and reduce the risk of fracture due to insufficient plasticity.
[0099] In summary, it is particularly important that the present invention provides a method for preparing a high-performance magnesium alloy suitable for prestressed loading conditions. By optimizing the alloy composition and preparation process, it aims to achieve effective control of the internal stress of the magnesium alloy, thereby improving the stability and reliability of the material under complex loading conditions. This method can not only solve the residual stress problem existing in traditional preparation technology, but also enhance the performance of magnesium alloys under extreme conditions, providing a safer and more reliable material selection for related applications. Through the implementation of this research, the adverse effects of prestress on the performance of magnesium alloys can be effectively reduced, and its application potential in high-demand environments can be improved, which will promote the further development and application of magnesium alloy materials.
[0100] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0101] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a high-performance corrosion-resistant magnesium alloy suitable for prestressed loading conditions, characterized in that: The following steps are involved: Pure Mg, pure Zr, Mg-30Gd master alloy, and Mg-30Y master alloy are used as raw materials, and 4.5wt.%~10.5wt.% Gd, 2.0wt.%~4.5wt.% Y, 0.3wt.%~0.6wt.% Zr, and the balance Mg, totaling 100%, are mixed and smelted; After smelting, it is refined and cast; After casting, the alloy is homogenized and hot extruded to obtain a high-performance magnesium alloy.
2. The method for preparing a high-performance corrosion-resistant magnesium alloy suitable for prestressed loading conditions according to claim 1, characterized in that: The melting temperature is 680°C~760°C.
3. The method for preparing a high performance magnesium alloy according to claim 1, characterized in that: The refining time is 5 minutes to 15 minutes.
4. The method for preparing a high-performance corrosion-resistant magnesium alloy suitable for prestressed loading conditions according to claim 1, characterized in that: The homogenization temperature is 380°C to 420°C, and the homogenization time is 10 hours to 14 hours.
5. The method for preparing a high-performance corrosion-resistant magnesium alloy suitable for prestressed loading conditions according to claim 1, characterized in that: The hot extrusion ratio is 14~18:1, and the extrusion speed is 0.5 mm / s~1.5 mm / s.
6. The method for preparing a high-performance corrosion-resistant magnesium alloy suitable for prestressed loading conditions according to claim 1, characterized in that: The casting mold preheating temperature is 200°C~300°C.
7. The method for preparing a high performance corrosion resistant magnesium alloy suitable for prestressed loading conditions according to claim 1, characterized in that: The stirring speed is 200RPM~400RPM.
8. A high performance corrosion resistant magnesium alloy suitable for prestressed loading conditions obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The high-performance corrosion-resistant magnesium alloy suitable for use under prestressed loading conditions comprises, by mass percentage, 4.5% to 10.5% Gd, 2.0% to 4.5% Y, 0.3% to 0.6% Zr, and the remainder is Mg, which totals 100%.
9. The high performance corrosion resistant magnesium alloy suitable for prestressed loading conditions according to claim 8, characterized in that: The high-performance corrosion-resistant magnesium alloy suitable for use under prestressed loading conditions comprises, by mass percentage, 7% to 10.5% Gd, 3% to 4.5% Y, 0.5% to 0.6% Zr, and the remainder Mg, which totals 100%.
10. Use of the high-performance corrosion-resistant magnesium alloy suitable for prestressed loading conditions as claimed in claim 8 in magnesium alloy parts under prestressed loading conditions.